Imaging features of desmoplakin arrhythmogenic cardiomyopathy: A comparative cardiovascular magnetic resonance study - Mikael Laredo; Etienne Charpentier; Shannon Soulez; Vincent Nguyen; Annamaria Martino; Leonardo Calò; Flavie Ader; Alexis Hermida; Véronique Fressart; Philippe Charron; Nadjia Kachenoura; Estelle Gandjbakhch; et al. (Journal of Cardiovascular Magnetic Resonance)
ABSTRACT: Background: Arrhythmogenic cardiomyopathy (ACM) related to Desmoplakin (DSP) mutations is a distinct condition associated with particularly severe outcomes, more frequent left ventricular (LV) involvement, including fibrosis, dysfunction, and inflammatory episodes. Whether DSP-ACM is associated with specific imaging features remains elusive. This study aims to provide a comprehensive description of cardiovascular magnetic resonance (CMR) findings in patients with DSP-ACM and to compare them to RV-dominant ACM with LV involvement (LV+ right-dominant-ACM). Methods: Patients with DSP-ACM matched with patients with ACM related to a non-DSP desmosomal mutation and ≥1 feature of LV involvement underwent CMR in two institutions. Biventricular metrics and segmental wall motion abnormalities (WMA) were assessed. LV late gadolinium enhancement (LGE) was assessed both qualitatively and quantitatively after semi-automated segmentation. Results: Overall, 70 ACM patients were analyzed; 37 with DSP-ACM and 33 in the LV+ right-dominant-ACM group. LVEF was significantly lower in the DSP-ACM group (46 ± 12%) than in the LV+ right-dominant-ACM group (56 ± 10%, P = 0.001). Conversely, RVEF was significantly higher in the DSP-ACM group (45 ± 11% vs. 40 ± 12%, P = 0.04) and both RV end-diastolic (100 ± 24 vs 130 ± 44 mL/m², P = 0.002) and end-systolic (56 ± 21 vs 81 ± 45 mL/m², P = 0.007) indexed volumes were significantly smaller in DSP-ACM as compared to the LV+ right-dominant-ACM group. The LV to RV end-systolic volume ratio (0.96 [interquartile range (IQR)0.70–1.27] vs. 0.59 [IQR 0.48—0.69]) was significantly higher in the DSP-ACM group (P < 0.0001), and had a good performance in differentiating both groups (area under the ROC curve 0.86, optimal threshold 0.8). Patients in the DSP-ACM group had significantly more LV and less RV WMA than those in the LV+ right-dominant-ACM group. The amount of LGE was significantly higher in the DSP group (14% ± 16 vs. 2%±3, P < 0.0001) and present in the majority of LV segments, particularly in the lateral and inferior walls, as compared to LV+ right-dominant-ACM patients. Transmural LGE and the presence of a ring-like pattern corresponding to circumferential subepicardial LGE involving ≥3 contiguous LV basal segments were highly specific of DSP-ACM. Conclusion: The presence of LV to RV end-systolic volume ratio>0.8, global LGE>5%, transmural and/or a ring-like LGE pattern are highly suggestive of DSP-ACM and should prompt careful diagnostic assessment considering the severe associated outcome.